CONTROLLING AS A MECHANISM TO INCREASE THE EFFICIENCY OF MANAGEMENT ENTERPRISES OF FUEL-ENERGY COMPLEX - M. A. Ostashkin (Модернизация, инновация, развитие, 2015)
This article discusses the possibility of application of controlling as mechanism of increasing the efficiency of management of enterprises of fuel- energy complex. The research was conducted on the materials of the JSC «Gazprom».